Liver Fibrosis Index FIB‐4 Is Associated With Mortality in COVID‐19. Issue 3 (10th December 2020) - Li, Yijia; Regan, James; Fajnzylber, Jesse; Coxen, Kendyll; Corry, Heather; Wong, Colline; Rosenthal, Alexandra; Atyeo, Caroline; Fischinger, Stephanie; Gillespie, Elizabeth; Chishti, Rida; Baden, Lindsey; et al.
Abstract : Coronavirus disease 2019 (COVID‐19) is associated with adverse outcomes, including need for invasive mechanical ventilation and death in people with risk factors. Liver enzyme elevation is commonly seen in this group, but its clinical significance remains elusive. In this study, we calculated the Fibrosis‐4 (FIB‐4) score for a cohort of hospitalized patients with COVID‐19 and assessed its association with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) RNA, inflammatory cytokine levels, and clinical outcome. A total of 202 hospitalized participants who tested positive for SARS‐CoV‐2 by nasopharyngeal sampling were included in this analysis. FIB‐4 was calculated for each participant using the alanine aminotransferase, aspartate aminotransferase, age, and platelet count. We evaluated the association between FIB‐4 and mortality using both multivariate logistic regression and Cox proportional hazards model. Correlations between FIB‐4 and SARS‐CoV‐2 RNA and cytokine levels were evaluated using the Spearman test. Among the 202 participants, 22 died. The median FIB‐4 in participants who survived and died were 1.91 and 3.98 ( P < 0.001 by Mann‐Whitney U test), respectively. Each one‐unit increment in FIB‐4 was associated with an increased odds of death (odds ratio, 1.79; 95% confidence interval, 1.36, 2.35; P < 0.001) after adjusting for baseline characteristics including sex, body mass index, hypertension, diabetes, and history of liver diseases. During hospitalization, FIB‐4 peaked and then normalized in the survival group but failed to normalize in the death group. FIB‐4 was positively correlated with the level of SARS‐CoV‐2 viral load and monocyte‐associated cytokines, especially interleukin‐6 and interferon gamma–induced protein 10. Conclusion: FIB‐4 is associated with mortality in COVID‐19, independent of underlying conditions including liver diseases. FIB‐4 may be a simple and inexpensive approach to risk‐stratify individuals with COVID‐19.